Subcellular location of antitumor tripeptide-tyroserleutide in human hepatocellular carcinoma cells - JIAN, XU (D.A. Spandidos, 2012)
Tyroserleutide (YSL) is a tripeptide compound that exhibits potent antitumor activity in human tumor xenografts and tumor cell lines. However, the target of YSL on which it exerts its antitumor activity has yet to be identified. Therefore, our study aimed to investigate the subcellular location of YSL in BEL-7402 human hepatocellular carcinoma cells. Using methods of fluorescent tracing and confocal colocalization, we provide evidence that when BEL-7402 cells are treated with YSL, YSL is distributed in the cytoplasm and colocalized with the mitochondria of cancer cells. Furthermore, we observed the effect of YSL on the isolated mitochondria. Using fluorescence spectrophotometry to monitor the Δψ collapse of mitochondria isolated from BEL-7402 cells by reversion of the quenching of tetramethylrhodamine methyl ester (TMRM), we found that the isolated mitochondria reversed the quenching of the fluorescence in the solution containing TMRM and YSL. This indicates that YSL decreases the Δψ of the isolated mitochondria. Another photometry method was used to observe the effect on mitochondrial swelling when YSL acted directly on the isolated mitochondria. We reveal that YSL directly causes mitochondrial swelling in 60 min. In conclusion, this study encloses a preliminary facet of the pharmacological target of YSL, and we speculate that YSL may act directly on the mitochondria to exert its antitumor activity.